Clinical Evaluation of an Unsintered Hydroxyapatite/Poly-L-Lactide Osteoconductive Composite Device for the Internal Fixation of Maxillofacial Fractures. Issue 6 (September 2016) - Sukegawa, Shintaro; Kanno, Takahiro; Katase, Naoki; Shibata, Akane; Takahashi, Yuka; Furuki, Yoshihiko
Abstract : Introduction: OSTEOTRANS MX (Takiron Co, Ltd, Osaka, Japan) is a resorbable osteosynthetic material composed of an unsintered hydroxyapatite/poly-l -lactide composite, and its osteoconductive capacity has been documented. The authors here report their clinical experience using OSTEOTRANS MX. Methods: The authors treated 35 patients (19 men, 16 women; age, 14–88 years; mean ± standard deviation, 38.4 ± 19.9 years) with maxillofacial fractures. The authors used standard surgery to stabilize fractures in all patients, fitting resorbable plates (thickness, 1.0 or 1.4 mm) and screws (diameter, 2 mm) according to Arbeitsgemeinschaft für Osteosynthesefragen/Association (AO) for the Study of Internal Fixation guidelines. Results: All patients eventually achieved satisfactory healing with favorable restoration of form and function without foreign body reaction. Complications occurred in 3 patients—plate exposure in 2 and discomfort in 1. However, fracture sites healed in all patients. Scanning electron microscopy revealed that the devices bonded directly to the bone without interposition of nonmineralized tissue. Conclusion: OSTEOTRANS MX is a useful material with few complications. Its osteoconductive bioactivity is advantageous for the early functional improvement of maxillofacial fractures.